2012
DOI: 10.1371/journal.pone.0048567
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Ki-67 by Dicer-Substrate Small Interfering RNA Sensitizes Bladder Cancer Cells to Curcumin-Induced Tumor Inhibition

Abstract: Transitional cell carcinoma (TCC) of the urinary bladder is the most common cancer of the urinary tract. Most of the TCC cases are of the superficial type and are treated with transurethral resection (TUR). However, the recurrence rate is high and the current treatments have the drawback of inducing strong systemic toxicity or cause painful cystitis. Therefore, it would be of therapeutic value to develop novel concepts and identify novel drugs for the treatment of bladder cancer. Ki-67 is a large nucleolar pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…)=acetylated lysine, p(ser. )=phosphorylated serine -increased expression of p53 and p73 [83,198] Ovarian -no change or increased expression of p53 [202,203] Erhlich Ascite carcinoma cells -increased expression of p53-ac(lys373) and total p53 [120] Colorectal cancer cells (LoVo, HCT116, p53-null HCT116, p53mutated HT29, p53-mutated Colo205)…”
Section: P53 Family Proteins Are Chemotherapeutic Targets Of Polyphenolsmentioning
confidence: 99%
“…)=acetylated lysine, p(ser. )=phosphorylated serine -increased expression of p53 and p73 [83,198] Ovarian -no change or increased expression of p53 [202,203] Erhlich Ascite carcinoma cells -increased expression of p53-ac(lys373) and total p53 [120] Colorectal cancer cells (LoVo, HCT116, p53-null HCT116, p53mutated HT29, p53-mutated Colo205)…”
Section: P53 Family Proteins Are Chemotherapeutic Targets Of Polyphenolsmentioning
confidence: 99%
“…Ki-67 is a large nucleolar phosphoprotein that participates the regulation of cell cycle and cell proliferation. Detailed cell cycle analysis revealed that Ki-67 antigen is present in the nuclei of actively proliferating cells (G1, S and G2 phase and mitosis) but not in the nuclei of quiescent or resting cells (G0 phase) [ 10 ]. The fraction of Ki-67-positive tumor cells (the Ki-67 labeling index) is often correlated with the clinical course of cancer patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the TCC cases are of the superficial type and are treated with transurethral resection (TUR). However, the recurrence rate is high and the current treatments have the drawback of inducing strong systemic toxicity or causing painful cystitis [4]. Therefore, efforts to develop a novel treatment to combat the disease with less side effects must necessarily be increased.…”
Section: Introductionmentioning
confidence: 99%